2000
DOI: 10.1126/science.290.5500.2302
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Linkage of Alzheimer's Disease to Chromosome 10q

Abstract: Recent studies suggest that insulin-degrading enzyme (IDE) in neurons and microglia degrades Abeta, the principal component of beta-amyloid and one of the neuropathological hallmarks of Alzheimer's disease (AD). We performed parametric and nonparametric linkage analyses of seven genetic markers on chromosome 10q, six of which map near the IDE gene, in 435 multiplex AD families. These analyses revealed significant evidence of linkage for adjacent markers (D10S1671, D10S583, D10S1710, and D10S566), which was mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
272
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(283 citation statements)
references
References 8 publications
(4 reference statements)
6
272
1
4
Order By: Relevance
“…In the total sample, Haplotype H2 carrying the intron 9/A allele suggested AD risk (p=0.06) and haplotype carrying the intron 9 /G allele suggested protection against AD risk (p=0.09) and these differences became significant among non-APOE*4 carriers (haplotype H2: p=0.0009; haplotype H3: p=0.0082). Recently a CHAT intron 10 SNP (rs2177369) was found to be associated with AD risk in a pilot sample of 202 cases and 295 controls, but not in a replication sample of 179 cases and 295 controls [2]. The intron 10 SNP is about 10 kb from the intron 9 SNP and it is likely that both SNP may be in LD, although their frequencies are different from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the total sample, Haplotype H2 carrying the intron 9/A allele suggested AD risk (p=0.06) and haplotype carrying the intron 9 /G allele suggested protection against AD risk (p=0.09) and these differences became significant among non-APOE*4 carriers (haplotype H2: p=0.0009; haplotype H3: p=0.0082). Recently a CHAT intron 10 SNP (rs2177369) was found to be associated with AD risk in a pilot sample of 202 cases and 295 controls, but not in a replication sample of 179 cases and 295 controls [2]. The intron 10 SNP is about 10 kb from the intron 9 SNP and it is likely that both SNP may be in LD, although their frequencies are different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage studies have identified several promising chromosomal regions to harbor additional AD genes, including chromosomes 12, 10, 9 and 6 [reviewed in 7]. A broad linkage peak encompassing >60 cM region between chromosome 10q21 and 10q25 that influence both AD risk and AAO has been suggested [2,4,10,13]. There are more than 300 genes in this broad genomic region of chromosome 10 and thus the task of identifying the chromosome 10 candidate gene is daunting.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] This is a problem because failure to identify causal variants within linkage regions may impede gene discovery. Part of the difficulty may be related to the analytical strategy using association-based methods to follow up linkage.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia cells degrade β-amyloid protein (Qiu et al 1998;Vekrellis et al 2000;Miners et al 2008), and this function is known to be altered in Alzheimer's disease (AD) (Bertram et al 2000) with the consequent noxious accumulation of the protein.…”
Section: Photoreceptor Nervous Cellsmentioning
confidence: 99%
“…Without the key example of AMD, it was previously hypothesized that AD was dependent upon the decline in function of these particular gliocytes determined by telomere shortening (Fossel 1996;Fossel 2004): "One function of the microglia ) is degradation of β-amyloid through insulindegrading enzyme (IDE), a function known to falter in Alzheimer disease (Bertram et al 2000)" (p. 233), and "telomere lengths of circulating monocytes can serve as an independent predictor in at least vascular dementia (von Zglinicki et al 2000)" (p. 235) (Fossel 2004).…”
Section: Photoreceptor Nervous Cellsmentioning
confidence: 99%